2019
DOI: 10.1002/asia.201901148
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl Sulfide (COS) Donor Induced Protein Persulfidation Protects against Oxidative Stress

Abstract: The emergence of hydrogen sulfide (H 2 S) as an important signallingm olecule in redox biology with therapeutic potentialh as triggered interesti ng enerating this molecule within cells. One strategy that has been proposed is to use carbonyl sulfide (COS) as as urrogate for hydrogen sulfide. Small molecules that generate COS have been shown to produce hydrogen sulfide in the presenceo fc arbonic anhydrase, aw idely prevalent enzyme. However,o ther studies have indicated that COS may have biological effects whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…NAD(P)H quinone oxidoreductase 1 (NQO1) is essentially involved in maintaining the cellular redox homeostasis, and constitutional upregulation of cellular NQO1 is frequently observed in response to oxidative emergencies 261–263 . Chakrapani et al reported an NQO1‐activatable H 2 S donor (donor 52 , Figure 7F) that bears a quinone motif as the substrate of NQO1 and a self‐immolative carbamothioate motif for COS/H 2 S generation 115 . As far as the donor 52 is concerned, NQO1 first catalyzes the transfer of two electrons from NADH to the quinone motif of donor 52 , leading to the generation of an active intermediate that goes through an intramolecular lactonization reaction, facilitated by a “trimethyl lock,” to liberate desired COS/H 2 S and mesalamine.…”
Section: H2s Donors and H2s‐releasing Hybrid Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…NAD(P)H quinone oxidoreductase 1 (NQO1) is essentially involved in maintaining the cellular redox homeostasis, and constitutional upregulation of cellular NQO1 is frequently observed in response to oxidative emergencies 261–263 . Chakrapani et al reported an NQO1‐activatable H 2 S donor (donor 52 , Figure 7F) that bears a quinone motif as the substrate of NQO1 and a self‐immolative carbamothioate motif for COS/H 2 S generation 115 . As far as the donor 52 is concerned, NQO1 first catalyzes the transfer of two electrons from NADH to the quinone motif of donor 52 , leading to the generation of an active intermediate that goes through an intramolecular lactonization reaction, facilitated by a “trimethyl lock,” to liberate desired COS/H 2 S and mesalamine.…”
Section: H2s Donors and H2s‐releasing Hybrid Moleculesmentioning
confidence: 99%
“…On this ground, H 2 S‐releasing agents (also named H 2 S donors) seem to be adequate for either mimicking the endogenous H 2 S generation under physiological conditions, or replenishing additional H 2 S for both diagnostic and therapeutical purposes. During the past years, substantial endeavor has been made to develop various H 2 S donors, and a number of H 2 S donors with different releasing rates and mechanisms have been reported 101,105–125 . H 2 S donors, regarded as the exogenous suppliers of H 2 S, could be employed as the ideal candidates for the treatment of diseases whose H 2 S‐associated networks might be short‐circuited.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of COS in human tissues suggests that it may also have regulatory roles in biology; however, our understanding of these roles remains limited. To advance future investigations into the biological roles of COS, a series of COS donors that are activated by different triggers have been developed. We reasoned that perthiocarbamates 1 may also produce COS in the presence of thiols as shown in Scheme , Path B. Under biological conditions, the RSSH released from Path A may react further with thiols to produce H 2 S. Similarly, COS generated from Path B would be converted to H 2 S by CA.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of plasma on the extracellular matrix can be decisive. Various studies have already demonstrated the effect of plasma on the EPS of biofilms ( Srey et al, 2014 ; Ziuzina et al, 2014 ; Bourke et al, 2017 ; Gilmore et al, 2018 ). Studies have shown that different species can produce various amounts of EPS ( O’Toole et al, 2000 ; Vu et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%